KEPEMILIKAN MANAJERIAL DAN PROFITABILITAS PERUSAHAAN TERHADAP NILAI PERUSAHAAN - nur widyawati (JOURNAL OF APPLIED BUSINESS ADMINISTRATION, 2021)
The purpose of this study is to determine: (1) The effect of partial and simultaneous between independent variables, namely managerial ownership and profitability of the company and the dependent variable, namely the value of the company. This type of research is quantitative research. The samples in this study were 21 banking companies listed on the Indonesia Stock Exchange in 2016 to 2018 and the sampling technique used purposive sampling techniques and data analysis techniques using multiple linear regression analysis methods. The results of this study stated that: (1) The managerial ownership variable (X1) partially did not affect Company Value. This means that the value of managerial ownership will not make the value of the company increase or decrease. (2) Profitability Variable (X2) partially influences Company Value. This means that if the company's ability to generate profits from the assets used increases, the company is increasingly in demand by investors so that the value of the company is increasing. (3) Simultaneously managerial ownership and profitability have an influence on Company Value.